2018
DOI: 10.3390/polym10080870
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur/Organic Copolymers as Curing Agents for Rubber

Abstract: It is widely acknowledged that waste sulfur generated from the petroleum industry creates huge storage and ecological problems. Therefore, the various methods of utilization are becoming increasingly attractive research topics worldwide. The thermal ability of elemental sulfur to homolytic cleavage of S8 rings enables its free radical copolymerization with unsaturated organic species and the obtaining of chemically stable polymeric materials. Here we report a novel possibility to use sulfur/organic copolymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
1
42
0
1
Order By: Relevance
“…Some residual sulfur did not participate in inverse vulcanization. These results were confirmed by Wręczycki [ 10 ] and Valle et al [ 36 ]. The results showed that the amount of sulfur had a great influence on the appearance of bio-based polysulfides.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Some residual sulfur did not participate in inverse vulcanization. These results were confirmed by Wręczycki [ 10 ] and Valle et al [ 36 ]. The results showed that the amount of sulfur had a great influence on the appearance of bio-based polysulfides.…”
Section: Resultssupporting
confidence: 73%
“…Orthorhombic sulfur (S α ) is the most thermodynamically stable form of elemental sulfur. S α presents in the form of eight-membered rings (S 8 ) [ 10 ]. The heating of S α leads it to be converted into monoclinic sulfur (S β , S 8 ) at 95.6 °C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The T g was found to be −17 °C for poly(S‐r‐Canola), −13 °C for poly(S‐r‐Rice Bran), and −24 °C for poly(S‐r‐Castor). DSC also revealed an endotherm between 100 and 150 °C, which corresponds to the transition of sulfur from an orthorhombic to monoclinic crystalline state and then melting and conversion to liquid sulfur ( Figure ) 31. An estimation of free, non‐polymeric sulfur content was made by integrating the area of these endothermic peaks after constructing a standard curve with crystalline S 8 standards (Supporting Information S24–S26).…”
Section: Resultsmentioning
confidence: 99%